(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This paper presents the design and implementation of a novel digital pulse-width modulation (PWM) signal generator for controlling DC-DC power converters. The proposed digital approach enables precise control of both the switching frequency and duty cycle of the PWM signals via a computationally efficient algorithm. This technique is versatile and can be integrated into various DC-DC converter configurations, thereby facilitating the development and experimental testing of new power-circuit designs. Experimental results demonstrate that the method offers significant advantages over traditional analog and digital techniques, including enhanced accuracy and improved signal quality. The performance of the proposed generator is validated through testing with a single-ended primary-inductance DC-DC converter (SEPIC). Additionally, the control board is suitable for both research and educational applications.